MONTHLY VARIABILITY OF TOTAL SUSPENDED MATTER (TSM) MAPPING USING MODIS 250M TO SUPPORT MARINE CULTURE AT MOROTAI ISLAND, NORTH MALUKU - SUNIADA, KOMANG IWAN (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2011)
This study was conducted to provide an information of Total Suspended Matter concentration and its monthly variability using dialy data of Terra/ Aqua MOD IS level 1 b with spatial resolution 250m imagery at Morotai Island, Northern Maluku. TSM is one of the water quality key parameter to support finding suitable area which is an important step for marine culture activity. Dialy Aqua/Terra MODIS level lb, 250m dataset was downloaded freely from Goddard Space Flight Center, LAADS Web (http ://ladsweb.nascom.nasa.gov/) and its contains information of calibrated radiance dan reflectance. TSM concentration derived using algorithm proposed by Trisakti et al, TSM (mg/I) = 72743 (bl+b2)2 ·3551, where bl is remote sensing reflectance band 1 and b2 is remote sensing reflectance band 2. Further process is daily TSM data composited to produce monthly data to define the variability. GIS application technique based on apropriate environment condition for fish comodity are used to mapping suitable area concerning of TSM parameter. Suspended sediment concentrations derived from satellite data showed that the average range of 40-90 mg/I, with the highest suspended sediment concentration occurred in January and lowest in June
Keywords: TSM, remote sensing, marine aquaculture